Analysis of solar photovoltaic module parks in Ukraine: Forecasting their further operation and end-of-life management - Karpash Maksym; Yavorskiy Andriy; Zhovtulia Liubomyr; Vasechko Valentyn (E3S Web of Conferences)
This article examines solar energy’s rapid growth and evolving role in Ukraine, focusing on the challenges and opportunities presented by the end-of-life management of photovoltaic (PV) modules. Despite only actively developing over the past decade, solar energy accounts for over 5% of Ukraine’s total electricity generation, ranking it 8th in Europe for installed PV capacity. The war in Ukraine has further underscored the importance of solar energy for the country’s energy security and resilience. However, with the majority of PV capacity installed only recently and with a finite lifespan, Ukraine will soon face significant volumes of decommissioned PV modules requiring processing, utilization, or reuse. The article highlights the urgency of developing a robust PV module recycling sector, as current practices involve landfilling most components. A comprehensive analysis of Ukraine’s PV module park, conducted as part of the EU-funded Retrieve project, represents a crucial first step towards effective PV waste management, aligning with Ukraine’s energy strategy and commitments under the Paris Agreement on climate change.